2020
DOI: 10.3389/fpsyg.2020.566977
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Activity of vmPFC Regulates Informational Social Conformity: A tDCS Study

Abstract: Social conformity has been evaluated in many different contexts, ranging from an emotional contagion in psychology, to speculative episodes in economics, to mass protests concerning politics. Previous neuroscience studies suggest that the ventromedial prefrontal cortex (vmPFC) participates in social conformity, especially when it comes to the value integration process, but the specific mechanism of vmPFC is still unclear. In this study, we aimed to identify a direct link between the vmPFC and conformity tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Activity of the VMPFC in this study was coupled with both ACC and PCC activation, depending on the specific offer with more PCC activation during unpleasant offers. Social variables that include evaluation, interaction, theory of mind, and empathy are also considered hot EFs and NIBS studies have shown that activation of the VMPFC modulates such social variables (Adenzato et al, 2017;Chib et al, 2013;Li et al, 2020;Salehinejad et al, 2020a). A recent tDCS study specifically investigated the interaction of the DLPFC and OFC in hot versus cold EFs by applying excitability-enhancing anodal and excitability-reducing cathodal stimulation (Nejati et al, 2018a).…”
Section: Nibs Studiesmentioning
confidence: 99%
“…Activity of the VMPFC in this study was coupled with both ACC and PCC activation, depending on the specific offer with more PCC activation during unpleasant offers. Social variables that include evaluation, interaction, theory of mind, and empathy are also considered hot EFs and NIBS studies have shown that activation of the VMPFC modulates such social variables (Adenzato et al, 2017;Chib et al, 2013;Li et al, 2020;Salehinejad et al, 2020a). A recent tDCS study specifically investigated the interaction of the DLPFC and OFC in hot versus cold EFs by applying excitability-enhancing anodal and excitability-reducing cathodal stimulation (Nejati et al, 2018a).…”
Section: Nibs Studiesmentioning
confidence: 99%
“…However, fNIRS uses relatively low spatial and temporal resolution. Electroencephalography (EEG) has been used to study affective states in the decision-making process (Li et al, 2020;Pei and Li, 2021). Due to the high temporal resolution of EEG, this neuroimaging tool has been widely employed to identify emotions, as an alternative to fNIRS or fMRI (Palmiero and Piccardi, 2017).…”
Section: Emotional Contagion In Neurological Reactionsmentioning
confidence: 99%
“…Furthermore, people who have a stronger conformity tendency show higher activation in the posterior medial frontal cortex and insula (Berns et al, 2010). During violations of expectations, increased activity in the anterior insula was found in both, social and non‐social contexts (Chang & Sanfey, 2013; Li et al, 2020)…”
Section: Neuronal Network Involved In Social Adaptationmentioning
confidence: 99%